Tenggerese Shaman as the Center of Cultural Continuity in Bromo Ngadas – East Java - Dika Sri Pandanari (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
Indigenous peoples have their own tendencies in structuring ethics and strengthening their identities. This has happened in various Indigenous communities, one of which is the Tengger people in Bromo Ngadas - East Java. This research was conducted through ethnological description on interviews for five months with the community and traditional officials to find out the role of shamans in indigenous peoples. Through this research it was found that the traditional shaman was the center of the Tengger community order. The role of the dukun or shaman can determine the identity of customs, ethics, and rules, as well as the distribution of power in society. Through this research it was also found that the preservation of the culture and economic life of the Tengger people was significantly influenced by the role of traditional shaman. The Shaman managing the ethics and spiritual continuity of the Tenggerese.